If it's not what You are looking for type in the equation solver your own equation and let us solve it.
41=-5c+6
We move all terms to the left:
41-(-5c+6)=0
We get rid of parentheses
5c-6+41=0
We add all the numbers together, and all the variables
5c+35=0
We move all terms containing c to the left, all other terms to the right
5c=-35
c=-35/5
c=-7
| -0.8x+-8.2=1.2x+5.8 | | -5(x+1)=-55 | | (2x+5)-(5x-4)=6-2(x-3) | | B/3+7=2a-7a+2 | | 2r-6=18 | | x+1/x^2-9=0 | | 61=7i-2 | | 36m-145=433 | | 9x=545 | | 2(6x+4)-6+2x=3(4x+3)-1 | | 5n+30=8n | | -5k-2=-17 | | (19x-4)-9(2x+4)=-3 | | 126y=21 | | 25x+200=500 | | 6g+12-4g+5=0 | | 2x-3x+5=10 | | a^2+7^2=15^2 | | 2x+(x+10)+44=180 | | 2-8p=66 | | 19x-7=18x | | 121=12h | | 5x3=14 | | 8.1+9a-8=8a | | 9-3x=-5-× | | -9x=-9-10x | | x/4-6=-9 | | 35-4x=(-1) | | 20x+600=1800 | | 42c=18 | | x^2-2x+26=1 | | 4(x-1)+6=-5(x+7) |